The crustal structure of the southern Nain and Makkovik provinces of Labrador derived from refraction seismic data - Funck, Thomas; Hansen, Annette K.; Reid, Ian D.; Louden, Keith E. (Canadian Journal of Earth Sciences, 2008)
Data from a refraction seismic profile parallel to the coast of Labrador (Canada) were used to determine the crustal structure across the boundary of the Nain and Makkovik provinces, and to look for evidence for an offshore continuation of the Mesoproterozoic Nain Plutonic Suite (NPS). Seven seismometers recorded airgun shots along the 283 km long line. P- and S-wave velocity models were developed from forward and inverse modeling of travel times. The velocity model distinguishes three distinct zones. In the Saglek block of the Nain Province, the crust is divided into three layers with P-wave velocities between 5.8 and 6.9 km/s. Farther to the south, upper crustal velocities increase to 6.3–6.5 km/s and the Poisson’s ratio increases from 0.24 to 0.27. This zone correlates with a gravity low that is interpreted to outline the offshore continuation of the NPS. The upper crustal velocities are intermediate between anorthositic and granitoid rock samples collected from the NPS. A lower crustal reflector is limited to the area underneath the NPS and may be related to dioritic magmas. Mid-crustal and lower crustal velocities do not vary along the line and no underplating was detected. Within the Makkovik Province, upper crustal velocities of 5.9–6.2 km/s may indicate a dioritic composition similar to the Island Harbour Bay plutonic suite. Moho depth varies between 28 and 36 km with the maximum beneath the NPS. The variations could not be linked to effects of the Makkovikian orogeny but are thought to relate to Mesozoic rifting in Labrador Sea.